RISK PERCEPTION FOR ACQUAINTANCE SEXUAL AGGRESSION: A SOCIAL-COGNITIVE PERSPECTIVE - Nurius, Paula S. (Aggress Violent Behav, 2000)
Beliefs that people hold about sources of harm and their personal susceptibility to harm have been shown to play an important role in their subsequent self-protection. With respect to acquaintance sexual aggression, women generally report low levels of perceived personal risk and, thus, low level preparedness to prevent or protect against this form of threat. In order to develop effective resistance efforts, a more complete understanding is needed of factors that shape perception of risk and how these factors are likely to influence—both positively and negatively—women’s risk reduction and self-protection. This article addresses this need by reviewing recent literature on risk perception and identifying relevant applications of theory and findings to women’s perception of risk for acquaintance sexual aggression.